2021
DOI: 10.1186/s12902-020-00651-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel GNAS mutation in pseudohypoparathyroidism type 1a in a Chinese man presented with recurrent seizure: a case report

Abstract: Background Pseudohypoparathyroidism is a rare genetic disease characterized by hypocalcaemia and hyperphosphataemia due to the defect to the guanine nucleotide-binding protein alpha subunit (GNAS) gene. Patients with pseudoparathyroidism type 1a and 1c could manifest Albright’s hereditary osteodystrophy and multiple hormone resistance including gonadotropin and thyroid stimulating hormone. Case presentation Here we report a Chinese man who presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Studies on thyroid imaging in iPPSD are insufficient (7,(23)(24)(25). Elli et al found normal thyroid scans in a cohort of patients (7).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Studies on thyroid imaging in iPPSD are insufficient (7,(23)(24)(25). Elli et al found normal thyroid scans in a cohort of patients (7).…”
Section: Figurementioning
confidence: 99%
“…There are few reports of thyroid ultrasound evaluation in iPPSD (7,(23)(24)(25). From a clinical paediatric endocrine standpoint, it is interesting and of practical value to determine how TSH resistance extrapolates to the ultrasound structure of the thyroid gland.…”
Section: Introductionmentioning
confidence: 99%
“…Several variants of PHP have been identified. The molecular defects in the GNAS gene encoding the alpha subunit of the stimulatory G protein (Gs α ) contribute to at least 3 different forms of the disease: PHP type 1a, PHP type 1b, and pseudopseudohypoparathyroidism 3 …”
Section: Introductionmentioning
confidence: 99%
“…PHP‐1 is further divided into three different subtypes: 1a, 1b, and 1c 3 . PHP‐1c, which is identical to PHP‐1a in terms of the presence of AHO and hormone resistance, but in contrast to PHP‐1a, in vitro assessment of Gs‐alpha protein activity, reveals no abnormality, and mutations of GNAS are usually not observed 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation